2019
DOI: 10.1016/j.tet.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase synthesis of biaryl cyclic peptides containing a histidine-tyrosine linkage

Abstract: A solid-phase strategy for the synthesis of biaryl cyclic peptides containing a side-chain to sidechain His-Tyr linkage was developed. The key step was the macrocyclization of a linear peptidyl resin incorporating a 5-bromohistidine and a 3-boronotyrosine via the formation of the biaryl bond by means of a microwave-assisted Suzuki-Miyaura reaction. This method allowed direct access to biaryl cyclic peptides containing a 3-or 5-amino acid ring and bearing the histidine residue at the Nor the C-terminus, being e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The diversity of synthetic peptides entering clinical trials has increased over the last 13 years, stimulating advances in Fmoc SPPS technologies in response to the growing demand for medicinal chemistry and pharmacology (Behrendt et al, 2016). Several groups have synthesized linear (Tran et al, 2008;Magliani et al, 2011;Konno et al, 2015;Cools et al, 2017;Park et al, 2018) and cyclic peptides (Mosca et al, 2000;Schaaper et al, 2001;Konno et al, 2015;Ng-Choi et al, 2019) using Fmoc SPPS.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…The diversity of synthetic peptides entering clinical trials has increased over the last 13 years, stimulating advances in Fmoc SPPS technologies in response to the growing demand for medicinal chemistry and pharmacology (Behrendt et al, 2016). Several groups have synthesized linear (Tran et al, 2008;Magliani et al, 2011;Konno et al, 2015;Cools et al, 2017;Park et al, 2018) and cyclic peptides (Mosca et al, 2000;Schaaper et al, 2001;Konno et al, 2015;Ng-Choi et al, 2019) using Fmoc SPPS.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…In fact, a scarce number of research groups has addressed the solid-phase synthesis of cyclic peptides incorporating a Phe-Phe, Phe-Tyr, Tyr-Tyr, Trp-Phe or a Trp-Tyr linkage (Afonso et al 2011(Afonso et al , 2012Meyer et al 2012;Mendive-Tapia et al 2015;García-Pindado et al 2017;Ng-Choi et al 2019a). In this context, we have recently developed a solid-phase strategy for the synthesis of biaryl cyclic peptides containing a His-Tyr bond (Ng-Choi et al 2019b). A linear peptidyl resin incorporating a 5-bromohistidine and a 3-boronotyrosine was used as precursor and the cyclization was performed through a microwave-assisted Suzuki-Miyaura cross-coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In order to build on their previous work employing MW-assisted Suzuki–Miyaura macrocyclization reaction [ 111 ], in 2020, Ng-Choi et al reported the MW-assisted synthesis of biaryl cyclopeptides via on-resin intramolecular Suzuki–Miyaura coupling [ 112 ]. Suzuki–Miyaura macrocyclization of 113 was performed on solid-support using Pd 2 (dba) 3 (0.2 eq), SPhos (0.4 eq), and KF (4 eq) in DME/EtOH/H 2 O (9/9/2) at 120 or 140 °C under MW irradiation for 30 min, followed by simultaneous resin cleavage and side-chain deprotections in TFA/TIS/H 2 O to provide 114 ( Scheme 33 ).…”
Section: Microwave-assisted And/or Solid-supported Synthesis Of Macro...mentioning
confidence: 99%